Open doors, no slots: Application of the change laboratory at the renal replacement therapy unit of a public hospital - Masiero, Cristiane Parisoto [UNESP]; de Almeida, Ildeberto Muniz [UNESP]; Querol, Marco Antonio Pereira; Buralli, Rafael Junqueira (Springer Nature, 2019)
The present chapter discusses the application of the Change Laboratory (CL) method at the hemodialysis service of a public hospital in Brazil. The initial context of the intervention was characterized by a high absenteeism rate among the nursing staff and reports of a crisis in the unit. The chapter describes an experience of the application of the method from management support to difficulties in the determination of the object of the activity. The problems detected derived from changes made in 2012, which resulted in the need for patients to stay several months at the hospital until slots for outpatient hemodialysis became available. Along this period, they received care from other hospital units. The intervention evolved along several stages, which required much learning from both researchers and staff to reconceptualize its object. Mirror data evidenced emotions which began to be shared, followed by critical analysis of contradictions. The resulting discussions enabled and encouraged initiatives for change in the organization of the activity.